2011
DOI: 10.1099/jmm.0.026781-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection and species identification of microsporidial infections using SYBR Green real-time PCR

Abstract: Diagnosis of microsporidial infections is routinely performed by light microscopy, with unequivocal non-molecular species identification achievable only through electron microscopy. This study describes a single SYBR Green real-time PCR assay for the simultaneous detection and species identification of such infections. This assay was highly sensitive, routinely detecting infections containing 400 parasites (g stool sample) "1 , whilst species identification was achieved by differential melt curves on a Corbett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…The tissue DNA extraction kit was chosen instead of the QIAamp DNA stool mini kit because, under these conditions, it yields higher quantities of parasite DNA and is more amenable to high throughput sample processing 9. Prior to extraction, each sample was supplemented with a standardised quantity of Escherichia coli transformed with a green fluorescent protein (GFP) gene to serve as the extraction and internal control10 together with the extraction control provided by Primerdesign in the G. intestinalis PCR kit.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue DNA extraction kit was chosen instead of the QIAamp DNA stool mini kit because, under these conditions, it yields higher quantities of parasite DNA and is more amenable to high throughput sample processing 9. Prior to extraction, each sample was supplemented with a standardised quantity of Escherichia coli transformed with a green fluorescent protein (GFP) gene to serve as the extraction and internal control10 together with the extraction control provided by Primerdesign in the G. intestinalis PCR kit.…”
Section: Methodsmentioning
confidence: 99%
“…These findings were supported by others who reported PCR is more sensitive(100%) compared to microscopic techniques in detecting microsporidial infection in HIV + patients 34,49,50 .The increased sensitivity of PCR can be attributed to lower threshold of microsporidia (10 2 spores/g stool) compared to optical microscopy in which the cut-off point ranges from 10 4 to 10 6 spores 51 . Althoughtrichrome staining is are liable and an available technique for detection of microsporidian spores in vitro, detection process is difficult and time-consuming for staining 46,52 .Moreover, higher prevalence of E. bieneusi compared to E. intestinalis has been reported in some studies 29,36,53 . While in one study in Egypt in cancer patients reported that E. intestinalis was the only species identified and the most prevalent in leukemic patients 46 .As shown in other studies, PCR could detect E. intestinalis (20%) and E. hellem (10%) in stool samples taken from cancer patients 20 , while Chabchoub et al found equal prevalence of E. intestinalis and E. hellem (33.3%) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Spencer et al described the use of SYBR Green real-time PCR assay for simultaneously detecting and identifying species of the disease causing Microsporidia using a new MsRTf1/MsRTr1 primer set which showed much greater sensitivity than that achieved by light microscopy and was equivalent to (or better than) that achieved by conventional PCR [37].…”
Section: Novel Molecular Methodsmentioning
confidence: 99%